Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran IPA Kelas VIII SMP Negeri 17 Tidore Kepuluan Pada Konsep Usaha - Kartini Lana (Peneliti.net, 2023)
The purpose of this research is to improve learning outcomes students in the subject of physics viii science class smpn 17 tidore kepuluan to the concept of business.The subject is students penenlitian class viii smpn 17 tidore kepuluan consisting 20 students. A model role playing is a way of mastery a lesson materials through the development of the imagination and penghayatan school tuition .The development of the imagination and penghayatan done school tuition with memerankannya as of a character living or inanimate objects .This game is generally carried out on more than one person , that it depends to those who played .The concept of economic undertakings are the forces acting upon a body so that the package to a displacement . The results of the study showed that in the cycle i and the cycles ii before and after learning the form of test that used the form of an essay that consisted of 10 item with a score total 100 .Students study results showed 20 people school tuition class viii , the five people who received a value of students low under a score flattened flattened as a whole output are unsatisfactory while students received a value of 15 people and he 75 % ) , in the cycle ii learning outcomes school tuition by using a model role playing showed a score above 75 % average of the application of the physics to the number of participants who could be classified as primary school students in 20 highest 97 %. As a result of this research that the application of the physics learners class viii smpn 17 tidore kepuluan academic year 2017 / 2018 can be improved through model role playing.